Bilateral Dorsal Subluxation of the Proximal Interphalangeal Joint of the Hind Limb in a Mare: Case Report - Pizzigatti, Dietrich [UNESP]; Hussni, Carlos Alberto [UNESP]; Rodrigues, Celso Antonio [UNESP]; Watanabe, Marcos Jun [UNESP]; Moura Alonso, Juliana de [UNESP]; Vulcano, Luiz Carlos [UNESP]; Cisneros Álvarez, Luis Emiliano [UNESP] (Elsevier, 2013)
Subluxation of the proximal interphalangeal joint is a rare and little studied condition in horses. We describe the case of a 12-year-old mare with bilateral dorsal subluxation of the proximal interphalangeal joint of the hind feet. Tenectomy of the medial digital flexor was performed in both limbs, and the patient showed signs of recovery within 14 days. Goniometry of the proximal interphalangeal joints 10 months after surgery showed diminution of 5° for the proximal interphalangeal axis of the left hind limb. However, no change was found for the joint angle of the right limb. Even so, the patient's gait and radiographic results were normal, and clinical abnormalities such as joint clicking and swelling were no longer observed. © 2013 Elsevier Inc.
Keywords: Medial digital flexor; Pastern; Proximal interphalangeal joint; Subluxation; Tenectomy; Equidae